2017
DOI: 10.1088/1674-1056/26/3/035201
|View full text |Cite
|
Sign up to set email alerts
|

Numerical study on the gas heating mechanism in pulse-modulated radio-frequency glow discharge

Abstract: The gas heating mechanism in the pulse-modulated radio-frequency (rf) discharge at atmospheric pressure was investigated with a one-dimensional two-temperature fluid model. Firstly, the spatiotemporal profiles of the gas temperature (T g ) in both consistent rf discharge and pulse-modulated rf discharge were compared. The results indicated that T g decreases considerably with the pulse-modulated power, and the elastic collision mechanism plays a more important role in the gas heating change. Secondly, the infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 28 publications
1
3
1
Order By: Relevance
“…Figure 10 shows that around 90% of the cyclic average power consumption P CA−PFM goes to gas heating through elastic collision, ion Joule heating, and exothermic reactions considered. It is observed that elastic collision and ion Joule heating are the dominant heating mechanisms contributing 23.9% and 65.8% of the power consumption, respectively, to the heating source, which is different from the simulated results obtained in [21,22] for helium discharges excited by the radio-frequency power sources showing that elastic collision is the dominant heating source. Although a few exothermic reactions release a large amount of energy in each reaction, the exothermic reactions considered contribute only a minor amount of energy to the heating source due to the low reaction rates.…”
Section: Analysis Of Power Consumptioncontrasting
confidence: 89%
See 4 more Smart Citations
“…Figure 10 shows that around 90% of the cyclic average power consumption P CA−PFM goes to gas heating through elastic collision, ion Joule heating, and exothermic reactions considered. It is observed that elastic collision and ion Joule heating are the dominant heating mechanisms contributing 23.9% and 65.8% of the power consumption, respectively, to the heating source, which is different from the simulated results obtained in [21,22] for helium discharges excited by the radio-frequency power sources showing that elastic collision is the dominant heating source. Although a few exothermic reactions release a large amount of energy in each reaction, the exothermic reactions considered contribute only a minor amount of energy to the heating source due to the low reaction rates.…”
Section: Analysis Of Power Consumptioncontrasting
confidence: 89%
“…The collisions of electrons and helium atoms contribute to more than 99.9% of the heating source of elastic collision while the collisions of electrons and N 2 molecules contribute to less than 0.1% of the heating source of elastic collision since the concentration of helium atoms is much higher than that of the N 2 molecules. frequency results in a remarkable contribution to the heating source as reported by other groups [9,21,22] in atmospheric pressure helium discharges. The collisions of electrons and helium atoms contribute to more than 99.9% of the heating source of elastic collision while the collisions of electrons and N2 molecules contribute to less than 0.1% of the heating source of elastic collision since the concentration of helium atoms is much higher than that of the N2 molecules.…”
Section: Elastic Collisionsupporting
confidence: 73%
See 3 more Smart Citations